Intersectional politics and citizen activism: An Israeli Mizrahi feminist lens - Daniele, G. (2023)
This article aims to rethink intersectional sites of solidarity carried out by coalitions of heterogeneous groups coming up from the margins of society. From this standpoint, I analyse intersectional politics through practices and processes led by feminist and other social justice grassroots activists together with citizen activists, that have helped give rise to political visibility of marginalised communities inside Israel. To address this issue, I critically discuss the interconnection of political intersectionality, coalition building, citizen activism, and its implications not only at the grassroots level, but also in local politics and institutions. This research is based on extensive fieldwork that took place in 2016 and 2018 in the most peripheral neighbourhoods of south Tel Aviv. In detail, I explore the role of one of the most well-known Israeli Mizrahi feminist movements called Ahoti (Sister) — for Women in Israel, in creating intersectional coalitions with other marginalised groups that mainly include long-term Mizrahi residents, non-Jewish African refugees and migrant workers. This cooperation between feminist activists historically engaged in grassroots movements together with citizen activists involved in new local struggles represents an original intersectional approach to multidisciplinary feminist research.